Caracterización de los agentes bacterianos casuales de Mastitis Bovina - Silva Goyes, Fanny Rosario (2021)
Bovine mastitis today continues to be one of the diseases that causes the greatest economic impact in dairy farms, being one of the most significant diseases from the point of view of milk production and public health. Due to the continuous contact with the animals and the mismanagement that occurs at the time of carrying out the milking methods either manually or mechanically, it has allowed the persistence of a series of pathogens. For the development of the bibliographic document, an exhaustive investigation was carried out, collecting bibliographic information from books, magazines, articles from web pages, technical manuals, projects. The objective of the research is the characterization of the causal agents of bovine mastitis. Pathology caused by more than 100 different species of pathogenic microorganisms and 95% of these infections are originated (in order of importance) by bacteria, they are: S. aureus, Streptococcus agalactiae, Streptococcus dysgalactiae, Streptococcus uberis, and S. epidermidis, the distribution of the agents that cause mastitis may be different, since in clinical cases the etiology may be due to bacteria that are present only for a short period of time, such as Escherichia coli, while subclinical mastitis can be caused by pathogens such as S. aureus, which can be present for long periods of time, producing only very slight signs on the cow's udder. In conclusion, whatever the causative agent of this pathology is (Gram Positive or Gram Negative) negatively influences the reproductive performance of cows, even the lesions that these bacteria can cause affect the mammary gland, for this, the bacteria must first penetrate, later adhere and finally invade the tissues.